2012
DOI: 10.1175/waf-d-11-00105.1
|View full text |Cite
|
Sign up to set email alerts
|

Objective Prediction of Warm Season Afternoon Thunderstorms in Northern Taiwan Using a Fuzzy Logic Approach

Abstract: In this study, a fuzzy logic algorithm is developed to provide objective guidance for the prediction of afternoon thunderstorms in northern Taiwan using preconvective predictors during the warm season (May-October) from 2005 to 2008. The predictors are derived from surface stations and sounding measurements. The study is limited to 277 days when synoptic forcing was weak and thermal instability produced by the solar heating is primarily responsible for thunderstorm initiation. The fuzzy algorithm contains 29 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 58 publications
(72 reference statements)
5
28
0
Order By: Relevance
“…The next question is what causes the projected decrease in CAR frequency over southwest Taiwan? Previous studies (e.g., Lin et al 2012;Huang and Wang 2014) examining the observational data suggested that the increase in daytime low-level wind convergence could provide more "dynamic" lift to facilitate CAR genesis. Using WRF-HiRAM and WRF-MRI as examples, the present-day simulations (Fig.…”
Section: Future Projectionsmentioning
confidence: 97%
See 1 more Smart Citation
“…The next question is what causes the projected decrease in CAR frequency over southwest Taiwan? Previous studies (e.g., Lin et al 2012;Huang and Wang 2014) examining the observational data suggested that the increase in daytime low-level wind convergence could provide more "dynamic" lift to facilitate CAR genesis. Using WRF-HiRAM and WRF-MRI as examples, the present-day simulations (Fig.…”
Section: Future Projectionsmentioning
confidence: 97%
“…Because of its importance to local residents, the characteristics and causes of CAR have been examined in many studies (Chen et al 1991;Johnson and Bresch 1991;Kerns et al 2010;Lin et al 2011;Huang and Chan 2012;Wang et al 2013). Studies have noted that CAR generally occurs on a day associated with a stronger sea breeze circulation during the daytime (e.g., Lin et al 2012). Such a temporal sea breeze circulation evolution is found to be consistent with the local temperature change (Huang and Wang 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have found that the maximum hourly rainfall of diurnal convection occurs at about 1600-1700 local time (LT) along the western slopes of the mountains (e.g., Chen et al 1999;WC08;Lin et al 2011). In point of fact, afternoon thunderstorms in Taiwan frequently caused flash floods, traffic interruptions, and power shortages due to lightning strikes; these associated hazards have caused human casualties.…”
Section: Introductionmentioning
confidence: 99%
“…Forecasters should examine the membership functions to ensure that they are reasonable for the dominant weather modes in their region. Lin et al (2012) suggest that the fuzzy membership functions themselves can be designed objectively using univariate conditional probabilities obtained from a longterm archive of data. Forecasters should also consider TABLE 6.…”
Section: Discussionmentioning
confidence: 99%